2019
DOI: 10.1111/fwb.13383
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term change of phytoplankton in Lake Kivu: The rise of the greens

Abstract: Phytoplankton time‐series enable the observation of recurrent seasonal patterns on community composition, but drastic shifts in community structure are rarely observed, unless linked to anthropogenic impacts (e.g. changes in nutrient inputs). Here, we report a unique case of non‐seasonal, multiannual regime shift of phytoplankton community structure in Lake Kivu, East Africa, and explore the possible causes for such changes. We recorded phytoplankton biomass every 2 weeks over a period of 12 years (from 2002 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 64 publications
5
20
1
Order By: Relevance
“…[e.g. 2 , 3 ], there are very limited data available on the water quality and ecological status of most lentic ecosystems in tropical Africa. From these data, it seems that growing eutrophication of these ecosystems [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[e.g. 2 , 3 ], there are very limited data available on the water quality and ecological status of most lentic ecosystems in tropical Africa. From these data, it seems that growing eutrophication of these ecosystems [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Vertical mixing in tropical lakes is very dynamic, and the depth of the actively mixing layer can range widely over 24 hr (e.g. Barbosa & Padisák, 2002;Rugema et al, 2019), as a function of water column heating due to solar radiation incidence, causing the actively mix layer depth to be shallower around noon (Amaral et al, 2018;MacIntyre & Melack, 1984). These daily vertical movements were shown to affect nutrients (Melack & Fisher, 1990) and greenhouse gases dynamics (Amaral et al, 2018(Amaral et al, , 2020Barbosa et al, 2020), but the impact to phytoplankton biomass and primary production on Amazon floodplain lakes are yet to be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Phytoplankton provides a substantial contribution to primary production in aquatic ecosystems (Zwart et al, 2015), sustaining a network of trophic interactions, with decisive consequences for ecosystem functioning (Abonyi et al, 2018). The role of bottom‐up factors influencing phytoplankton biomass has been studied for decades, but prevailing models developed in temperate zones may be inappropriate for tropical environments due to differences in food web configuration and varying amplitude of seasonal and interannual cycles (Huszar et al, 2006; Melack, 1976; Rugema et al., 2019; Sarmento, 2012). Phytoplankton biomass is regulated by both top‐down and bottom‐up effects in temperate lakes distributed over a wide productivity gradient (Mazumder, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Since 2002, phytoplankton studies have been conducted in Lake Kivu (Sarmento et al 2012, Rugema et al 2019) using high performance liquid chromatography (HPLC) to determine phytoplankton marker pigments. This technique, which can estimate phytoplankton biomass at the class level, was developed in the marine environment (Wright and Jeffrey 2006) and applies as well to estuarine and fresh waters (Fietz and Nicklisch 2004, Descy et al 2005, Fietz et al 2005, review in Sarmento and Descy 2008.…”
Section: Introductionmentioning
confidence: 99%
“…This technique, which can estimate phytoplankton biomass at the class level, was developed in the marine environment (Wright and Jeffrey 2006) and applies as well to estuarine and fresh waters (Fietz and Nicklisch 2004, Descy et al 2005, Fietz et al 2005, review in Sarmento and Descy 2008. Monitoring phytoplankton biomass and composition in Lake Kivu, based on the use of specific marker pigments of these classes over 12 years, allowed Rugema et al (2019) to detect dramatic changes in phytoplankton community structure of Lake Kivu, which they attributed to a change in the water column mixing pattern, depending on large-scale climate variability. That study demonstrated the potential of using pigmentbased analysis of phytoplankton composition, complemented by data from microscopy, as a tool to monitor environmental changes in this tropical lake at different time scales.…”
Section: Introductionmentioning
confidence: 99%